Influência do clima no número de hospitalizações por nefrolitíase, em regiões urbanas no Brasil. Um estudo coorte retrospectivo de seis anos - Abreu-Júnior, João de (2018)
Introduction: Nephrolithiasis has a worldwide prevalence of approximately 5% to 15%, and its occurrence is associated with age, sex, race, dietary habits, geographic location, climatic conditions, and other factors. Objective: To determine the association between climate and the number of hospitalizations for nephrolithiasis (NHNL) in Brazilian cities located in different climatic regions. Methods: We analyzed data from cities with tropical and subtropical climates. The effects of minimum (LT), mean (MT), maximum (HT) mensal temperatures and relative humidity of the air (RH) were assessed. Results: A positive associations were found between the number of hospitalizations for nephrolithiasis and temperature (LT x NHNL; R2=0.218; P<0.0001), (MT x NHNL; R2=0.284; P<0.0001), (HT x NHNL; R2=0.317; P<0.0001) and a negative association with relative humidity (RH x NHNL; R2=0.234; P<0.0001). Interactions were also observed between MT and RH with respect to their effect on NHNL, as described by a linear model (NHNL = 4.688 + 0.296 x MT – 0.088 x RH). NHNL was higher in cities with tropical climates than in cities with subtropical climates (82.4 + or - 10.0 vs 28.2 + or - 1.6; P<0.00001). Conclusion: There is an association between NHNL and variations in temperature and relative humidity.